2014
DOI: 10.1007/s00213-014-3664-5
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine administration in depressive disorders: a systematic review and meta-analysis

Abstract: The present meta-analysis confirms ketamine's efficacy in depressive disorders in non-ECT studies, as well as in ECT studies. The results of this first meta-analysis are encouraging, and further studies are warranted to detail efficacy in bipolar disorders and other specific depressed populations. Middle- and long-term efficacy and safety have yet to be explored. Extrapolation should be cautious: Patients included had no history of psychotic episodes and no history of alcohol or substance use disorders, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
222
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(233 citation statements)
references
References 31 publications
7
222
1
3
Order By: Relevance
“…Although the clinical effect of ketamine is mainly attributed to blockade of GluN2B NMDAR (Fond et al, 2014;McGirr et al, 2014), our results show that GluN2A-NMDARs located on afferent terminals of the VM are the most likely source of inhibition that modulates reward seeking, suggesting a complex circuitry that was not fully appreciated in prior pharmacological studies. Our results suggest that a dysregulation or an enhancement of VM GluN2A-mediated neurotransmission can lead to severe alteration of mood characterized by anhedonia.…”
Section: Discussionmentioning
confidence: 61%
“…Although the clinical effect of ketamine is mainly attributed to blockade of GluN2B NMDAR (Fond et al, 2014;McGirr et al, 2014), our results show that GluN2A-NMDARs located on afferent terminals of the VM are the most likely source of inhibition that modulates reward seeking, suggesting a complex circuitry that was not fully appreciated in prior pharmacological studies. Our results suggest that a dysregulation or an enhancement of VM GluN2A-mediated neurotransmission can lead to severe alteration of mood characterized by anhedonia.…”
Section: Discussionmentioning
confidence: 61%
“…The present results imply that changes in glutamine/glutamate are different from the acute brain effects during infusion of subanesthetic ketamine. The potential reversal of a pathologically reduced glutamine/glutamate levels as measured in terms of their ratios, as found in MDD, appears to be maximal after 24 h when the acute dissociative effects have vanished, but when the antidepressent effects are at their peak (Caddy et al, 2014;Fond et al, 2014;McGirr et al, 2015;aan het Rot et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…40 Recent studies have shown a rapid antidepressant effect after a single dose of intravenous ketamine alone, or as an adjunct to antidepressants, in both unipolar and bipolar depression. 41 Repeated administration maintains improvement but relapse occurs rapidly on stopping treatment. 42 …”
Section: Clinical Use Of Electroconvulsive Therapymentioning
confidence: 99%